Segmental volvulus of the ileum without malrotation in an infant: A case report - Younglim Kim; Suk-Bae Moon (Elsevier, 2015)
Intestinal volvulus usually occur secondary to malrotation, and primary segmental volvulus has rarely been reported. A 12-month-old female infant presented with a 3-day history of excessive vomiting. An ultrasonography revealed a "whirlpool sign" in the right upper abdomen, suggesting small bowel volvulus with obstruction. Laparotomy revealed a twisted, viable loop of small bowel in the right upper abdomen, and abnormal adhesions were noted between the distal and mid ileum, with resulting mesenteric narrowing. Attempted mesenteric widening by dissection of the peritoneum overlying the adhesions failed, because of abnormal, taut mesenteric vessels. Subsequent resection of the involved segment cured the patient. Recurrent obstructive symptoms in an infant can be an atypical presentation of segmental volvulus, and segmental volvulus should be included in the differential diagnosis of such cases.